15 fabulous magical stories for young readers 2 - Anand;Paro (Selangor Maxim press)
This marvelous book is a compilation of creative and fabulous stories depicting positive perspectives within the learning of the young child. The stories together with full-colored illustrations will no doubt enhance the children$1 (Bs quest for reading and telling stories. It is a perfect and most entertaining way to would young children into liking stories and thereafter telling them to others.s